Effect of scarification on biochemical activities of aged seeds of guava (Psidium guajava) - Kumari, Santosh; Malik, Arvind; Mor, Rajesh; Kumar, Sonu; Jat, M. L.; Jaipal, Jaipal (Current Horticulture, 2023)
The study was carried out on fresh, one, two and three years aged seeds of guava (Psidium guajava L. ) L-49 (Sardar) in the laboratory of Department of Seed Science and Technology, CCS HAU, Hisar, during 2018-2019. The seeds were subjected to different seed scarification treatments, viz. hot water treatment at 80°C for 1 minute, concentrated sulphuric acid for quick dip and water soaking for 48 hr. The seeds were assessed for peroxidase activity, dehydrogenase activity and electrical conductivity. Hot water treatment at 80°C for 1 minute resulted into maximum peroxidase activity (710.0) and dehydrogenase activity (0.233) with minimum electrical conductivity (11.02). It is concluded that seeds treated with hot water treatment at 80°C for 1 minute showed maximum peroxidase, dehydrogenase activities and minimum electrical conductivity which reflects better seed quality.